Why multinational enterprises may be causing more inequality than we think. Issue 3 (16th September 2019) - Giuliani, Elisa
Abstract : Purpose: This paper aims to discuss the ways in which multinational enterprises (MNEs) may contribute to growing inequality. Design/methodology/approach: By showing some macroscopic evidence of business-related human rights infringements, this paper claims that the negative impacts of MNEs has been largely overlooked. Findings: The extent to which MNEs contribute to income-based inequality through the abnormal accumulation of wealth by chief executive officers (CEOs), top managers and shareholders is known, and almost nothing is known about whether this is connected to MNEs' track record of human rights infringements. Originality/value: This paper suggest that there might be a connection between MNEs' human rights infringements and the abnormal accumulation of wealth by companies' CEOs, top managers and shareholders. It calls for more international business research investigating this link.